Explanation:
We will prove by mathematical induction that, for every natural n,
![(x-y)(x^(n)+x^(n-1)y+...+xy^(n-1)+y^(n))=x^(n+1)-y^(n+1)](https://img.qammunity.org/2020/formulas/mathematics/college/qimfg7jq6zqp1y7hxo9d9hjyfgac1yk4m3.png)
We will prove our base case (when n=1) to be true:
Base case:
![(x-y)(x^(n)+x^(n-1)y+...+xy^(n-1)+y^(n))=(x-y)(x^(1)+y^(1))=x^2-y^2=x^(1+1)-y^(1+1)](https://img.qammunity.org/2020/formulas/mathematics/college/fbegci6w9tkk3iqgl9snynaqclk7gbg4sa.png)
Inductive hypothesis:
Given a natural n,
![x^(n+1)-y^(n+1)=(x-y)(x^(n)+x^(n-1)y+...+xy^(n-1)+y^(n))](https://img.qammunity.org/2020/formulas/mathematics/college/to4wzkcf1nx18689i2j0mu9uwyh3ijkico.png)
Now, we will assume the inductive hypothesis and then use this assumption, involving n, to prove the statement for n + 1.
Inductive step:
Observe that, for y=0 the conclusion is clear. Then we will assume that
![y\\eq 0.](https://img.qammunity.org/2020/formulas/mathematics/college/j0mms27za9ykkg0sdai6z9q6al7mbhkfps.png)
![(x-y)(x^(n+1)+x^(n)y+...+xy^(n)+y^(n+1))=(x-y)y((x^(n+1))/(y)+x^(n)+...+xy^(n-1)+y^(n))=(x-y)y((x^(n+1))/(y))+(x-y)y(x^(n)+...+xy^(n-1)+y^(n))=(x-y)y((x^(n+1))/(y))+y(x^(n+1)-y^(n+1))=(x-y)x^(n+1)+y(x^(n+1)-y^(n+1))=x^(n+2)-yx^(n+1)+yx^(n+1)-y^(n+2)=x^(n+2)-y^(n+2)\\](https://img.qammunity.org/2020/formulas/mathematics/college/qlftb1husvr9w72bsssie7gj0w6t5w4swt.png)
With this we have proved our statement to be true for n+1.
In conlusion, for every natural n,
![(x-y)(x^(n)+x^(n-1)y+...+xy^(n-1)+y^(n))=x^(n+1)-y^(n+1)](https://img.qammunity.org/2020/formulas/mathematics/college/qimfg7jq6zqp1y7hxo9d9hjyfgac1yk4m3.png)